মজলিস - মুখোপাধ্যায়, কুমারপ্রসাদ (কলকাতা : আনন্দ পাবলিশার্স, 1997)
Anecdotes from the life of some Indian classical singers and musicians of Hindustani school; reminiscences by singer and music critic.
Akbar Ali Khan Collections
Keywords: মুখোপাধ্যায়, কুমারপ্রসাদ, -- ১৯২৭-২০০৬; Singers -- India -- West Bengal -- Biography; Music -- India -- History and criticism; Musicians -- India -- West Bengal -- Biography; Hindustani music -- History and criticism